The Effect of Using the Interaction Simulation Video to Enhance Digital Empathy Skills - Jamsai, Pattaraporn; Chuensombat, Suebwong; Locharoenrat, Weeramol; Maneenil, Sirikanya (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This research aims to investigate the impact of using interactive simulation videos on enhancing digital empathy skills. The study involved 300 high school students from three schools in Bangkok, Thailand. The participants were chosen using the multistage sampling method. The research instruments included: (1) an interactive simulation video; (2) a digital empathy skills test; (3) a satisfaction assessment; and (4) an interview form. The data were analyzed using a dependent t-test, mean, standard deviation, percentage, and qualitative data analysis. The research found that (1) participants’ digital empathy skills scores improved significantly at the 0.05 level, (2) participants’ overall satisfaction was high (x = 4.48), and (3) all participants agreed that the interactive simulation video was appropriate, helped them improve their digital empathy skills, and was suitable for use as teaching material. An interactive simulative video contains various elements that enhance students’ digital empathy skills, including embedded questions, overlays, and hotspots.